Significance of serum heat stable alkaline phosphatase as a marker in lung cancer - Al-jassani, Jasim Mohammed H. (Al-Qadisiyah Journal of Pure Science, 2017)
The objective of this study is the evaluation of serum levels of heat stable alkaline phosphatase(HSAP) as marker in lung cancer. The study include 44 lung cancer patients with and without metastases and 30 matched healthy individuals. It has been found a significant elevation (p<0.001) in patients with metastase and(p<0.01) in patients without metastases for biomarker, in sera of patients in comparison to the health subjects. A decreaese in the levels of the biomarker was apparently significant after removal of the malignant tumor. However multiple post-operative determinat of HSAP showed continuing elevation of the biomarker above the normal value in patients who developed metastases. The results indicate that the HSAP can be used as a marker in the detection and prediction of metastases in lung cancer.